Stock Performance and Intermediation Changes Surrounding Sustained Increases in Disclosure* - HEALY, PAUL M.; HUTTON, AMY P.; PALEPU, KRISHNA G. (Contemporary Accounting Research, 1999)
Abstract This paper investigates whether firms benefit from expanded voluntary disclosure by examining changes in capital market factors associated with increases in analyst disclosure ratings for 97 firms. The disclosure rating increases are accompanied by increases in sample firms' stock returns, institutional ownership, analyst following, and stock liquidity. These findings persist after controlling for contemporaneous earnings performance and other potentially influential variables, such as risk, growth, and firm size. While it is difficult to draw unambiguous causal conclusions, these results are consistent with disclosure model predictions that expanded disclosure leads investors to revise upward valuations of the sample firms' stocks, increases stock liquidity, and creates additional institutional and analyst interest in the stocks.